PENGEMBANGAN MODEL BIMBINGAN KELOMPOK TEKNIK OUTBOUND UNTUK MENINGKATKAN KOMUNIKASI ANTAR PRIBADI MAHASISWA - Mulyani Mulyani; Rinie Tri Herdiani (Universitas Negeri Surabaya, 2018)
In everyday life, interpersonal communication will always happen no exception in the campus environment. Interpersonal communication skills among students is beragam.Seperti case in Tegal UPS campus environment, based on our observations of the student FKIP UPS Tegal particularly Prodi Guidance and Counseling. Students who have good interpersonal communication have an indication as easy to get along, actively organize, many friends, sensitive to the environment, dll.Tujuan of this study was to determine: 1) the real condition of interpersonal communication between students before the implementation of outbound group counseling techniques, 2) for interpersonal communication students after the implementation of the Guidance Group Outbound Techniques ?, 3) to Know apakalah Outbound Engineering Group Guidance models can improve inter-personal communication Mahasiswa.Metode this study is accordance with the problems and research objectives, this research using this type of research and development or research and Development (R & D), which is a type of research that is used to produce a particular product, and test the effectiveness of these products (Borg & Gall in Sugiyono 2010: 407-409) the results was that the study of interpersonal communication students before administration of group counseling services den gan outbound engineering student interpersonal communication before the given group counseling service with outbound techniques, producing interval 103-108, as many as 12 students with a percentage of 40% were classified in the low criteria interpersonal communication students after the administration of guidance services research group with outbound techniques produce interval 121-126, as many as 15 students with a percentage of 50% belonging to the high criteria. Based on the analysis with statistical calculations using t-test is obtained t = 4.763 with 1% significance level and degrees of freedom N-1 = 30-1 = 29, then gained the table = 2.756. It can be concluded that the Model Guidance Outbound Engineering Group can improve interpersonal communication students Prodi BK FKIP UPS Tegal.Kesimpulan that guidance services group, has an important role in developing the ability to interact or communicate as well as to improve communication between students